Challenges Encountered by SMEs in Tourism Industry: A review from 2017 to 2021 - Adilah Md Ramli; Putriku Nuraishah Khairanni Asby; Harifah Mohd Noor; Teuku Afrizal (e-International Publishing House, U.K, 2022)
The tourism industry worldwide has decreased because of restrictions on the entry of tourists due to the pandemic of Covid19. This study explores the challenges SMEs face through this pandemic through literature studies. The systematic literature review (SLR) method was used to examine and analyses all extant research articles published in Google Scholar from 2017 to 2021. Articles analysed by the keywords: SMEs, Challenge, and Tourism. Based on the findings, the challenges faced by SMEs can be categorised into internal and external factors that may influence SMEs, especially in the tourism industry, which includes the food industry.